Znaczenie figur mitycznych Apolla i Dionizosa w twórczości Zbigniewa Herberta - Hejniak, Zuzanna (Prace Polonistyczne, 2023)
The article aims to fill in a research gap – the lack of a sufficiently comprehensive description of the transposition of myth in the works of Zbigniew Herbert. The pair of gods selected by Hejniak primarily serves as a symbolic representation of Herbert’s own attitude to reality. A chronological analysis of his works leads to a conclusion that the poet is more tender towards Dionysus. By contrast, Apollo is the god in whom Herbert placed the greatest hopes, and, paradoxically, it was through this mythical figure that he expressed his strong faith in modernity.